Per una filologia del copione: Adelaide Ristori e ‘Lady Macbeth’ - Chichiriccò, Emanuela (Drammaturgia, 2024)
Adelaide Ristori’s Macbeth is an interesting object for a study in the field of theatrical philology. In Ristori’s Archive at Museo Biblioteca dell’Attore in Genoa there are in fact many unpublished and little-valued materials which can be profitably used for the reconstructions of the metamorphosis of Ristori’s Macbeth over the 30 years that elapse between its complex (and still obscure) creation and its last performance. In fact, among the more than five hundred different dramaturgical writings kept in the Ristori Archive there is a vast section dedicated to Macbeth and its rewritings that meticulously documents the various phases of the work’s life. These materials, usually accompanied by epistolary, autobiographical, critical and iconographic documents, are here placed at the centre of the investigation, organised and interrogated with the tools of textual philology. The study of the literary materials relating to Macbeth provides a solid basis for the reconstruction of the scenic writing of the play and thus of Ristori’s work on the script, her cultural interests, the organisational system of her company and the network of international relations that sustained the editorial and compositional dynamics of her performances.